THE ROLE OF POLICY IN THE EXERCISE OF DISCRETION: A COMPARATIVE SEARCH FOR FAIRNESS - DOI 10.5935/2448-0517.20200039 - Jansen, Friso (Juris Poiesis - Qualis A3, 2020)
The executive in implementing the wishes of parliament is often faced with a problem of allocation. How to distribute limited resources and exercise the discretion afforded to the executive in such a way that this is both procedurally and substantively fair? The answer lies in the formulation of a policy. Through clear and transparent procedures citizens would be treated equally, therefore delivering administrative justice. Different countries, however, seem to prioritize different conceptions of fairness and equality. While in English administrative law the focus is placed on the need for a scrutiny of the individual circumstances of a claimant to avoid fettering discretion in Dutch administrative law the stress is placed on the claimant to prove he should be treated differently to the standard case envisaged in a policy document. The question becomes whether on closer inspection these theoretical differences in approach reveal differences in practical application. This paper will try to answer some of these questions based on a comparative reading of law and jurisprudence from both countries.